Pengaruh Administrasi Pendaftaran, SDM, Sarana dan Prasarana terhadap Faktor-faktor yang Memengaruhi Waktu Tunggu Pasien di IGD RSUD Junjung Besaoh - Faguita Sona Putri; Lilis Lisnawati; Aliefety Putu Garnida (SENTRI: Jurnal Riset Ilmiah, 2026)
Waiting time for health services in the emergency department is one of the most sensitive components of service quality assessment and a major concern in the Minimum Service Standards (SPM) for hospitals. Therefore, emergency department management must consider all aspects that can affect waiting time holistically, from administrative processes and workforce capacity to the availability of supporting facilities and infrastructure. The purpose of this study is to determine the influence of registration administration, human resources, and facilities and infrastructure on the factors affecting patient waiting times in the ED of Junjung Besaoh General Hospital. This study is quantitative research. Data collection was conducted by distributing questionnaires to 96 respondents, and multiple linear regression was used to examine the effects of the independent variables on patient waiting times. The results show that registration administration, human resources, and facilities and infrastructure significantly affect patient waiting times, with an $R2$ value of 0.78, indicating that these three variables explain 78% of the variance in waiting times. Among them, human resources had the most significant influence. This indicates that improvements in registration administration, human resources, and infrastructure are associated with shorter patient waiting times in the Emergency Department of Junjung Besaoh General Hospital.